Pengaruh Model Pembelajaran Needham terhadap Pemahaman Konsep Trigonometri - Venty Meilasari; Ratih Handayani; Mira Refiasari (Eksponen, 2023)
Abstract: The purpose of this study was to determine whether the Needham learning model had a positive effect on students' understanding of trigonometric concepts. The research methods used are experimental and the study design used is quasi-experimental involving only post-tests. The study population consisted exclusively of students in Class X of Madrasah Aliya Al-Mubarok for the 2021/2022 school year. The samples in this study were classes X IPA 1 and X IPA 2 drawn using a cluster random sampling technique. Correct t-test statistics were used for data analysis. Based on the results of data analysis obtained 3.617 and 1,678. Based on these results, obtained , it can be concluded that there is a positive effect of the application of the Needhaam learning model on students' understanding of concepts. Keywords: Needham Learning Model; Concept Understanding; Trigonometry